VIRTUAL AGRICULTURAL MARKETS – TRENDS AND CHALLENGES - M. Petrov; E. Delcheva (Trakia Journal of Sciences)
In recent years, a process of restructuring of farms in Bulgaria has been observed, which consists in the modernization of agricultural markets through the use of different platforms. This change is associated with many challenges for farmers, as well as following certain trends in the agricultural sector. The purpose of the research is to trace to what extent innovations are imposed in the economic sector, where the production is available on the virtual market. Innovations in virtual agricultural markets allow quality fresh produce to reach a greater number of end consumers. Research methods are prospecting and analysis of the current platforms for trading agrarian products: electronic stores, social networks, sites, applications for direct sales. The results of the research show that there are a wide range of opportunities to participate in virtual agricultural markets and they support the development of farms, but at the same time they are associated with challenges and important problems in the realization of agricultural production. Following and developing modern market trends is necessary for adapting manufacturers to the constantly changing market environment and increasing their competitiveness. As a result, virtual agricultural markets are developing as a means of sustainable commercial relationships and represent an alternative for easy access of agricultural products to consumers.